(untitled) (Journal of Oriental Studies, 2016)
the article is devoted to one of the most important problems in the military translation – the problem of the military terminology. the author of the article describes the definitions of the lexical units «terM» and «Military terM». the most important peculiarities of the Japanese military terms are analyzed.